ANALISIS LINGKUNGAN FISIK RUMAH SEBAGAI FAKTOR RISIKO KEJADIAN PNEUMONIA PADA BALITA DI INDONESIA (DENGAN KAJIAN SISTEMATIS) - Restiana, Shafira Azura; Raharjo, Mursid; Suhartono, Suhartono (Jurnal Kesehatan Masyarakat (Undip), 2021)
Pneumonia is one of the leading causes of toddler mortality in worldwide, owing to several important risk factors such as home physical environment. The role of each physical home environment for Pneumonia is still uncertain. The study aims to evaluate each various of the physical home environment impact to Pneumonia in toddlers. The search is limited and focused in International and Nasional journals published in 2016-2019. Researches has reviewed 24 articles that matched with the inclusion criteria, 4 studies were conducted with a cross-sectional approach while the rest were conducted with a case-control approach. Overall, several articles were showed a relationship between these risk factors and the incidence of Pneumonia in toddlers, 5 articles of floor type (20,8%), 3 articles of house wall conditions (12,5%), 13 articles of house lighting (54%), 22 articles of home ventilation (91,6%), 8 articles of house occupancy density (33,3%), 3 articles of house temperature (12,5%), and 7 articles of smoking presence (29,2%). These results can be concluded that there are three dominant risk factor:  ventilation, lighting and house occupancy density. People are advised to ensure that the area of house ventilation is suit with the requirements to allow natural lighting enter the house and ideal occupancy density thereby reduce the possibility of pneumonia-causing pathogens transmission in toddlers.